Increasing Spiritual Intelligence as an Effort to Fortify the Younger Generation from the Depravity of the Times - Hutabarat, Jansen (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Only in 2021, 350 thousand complaints of rape were registered in Indonesia. 63% of campus violence incidents were not reported to maintain the good image of the campus. Spiritual intelligence may reduce juvenile delinquency among college students. Spiritual intelligence is used as a foundation to maximize intellectual intelligence and emotional intelligence. With spiritual intelligence, a person sees that every life has meaning and value, which makes the individual feel useless in reality. The Bible teaches that followers of Christ, including Christian students, must have the character of Christ and live according to the truth, which means living without the mask of hypocrisy. The inherent responsibility of Christian students should include a desire and commitment to learn and develop their Christian character so that their lives will radiate the glory of the Lord Jesus Christ.